Biosimilars are essential for sustainable healthcare systems; however, key challenges remain as seen with long-acting insulin analogues - Brian Godman, Biljana Tubic, Eleonora Allocati, Magdalene Wladysiuk, Stuart McTaggart, Amanj Kurdi&& , Mainul Haque,Sean MacBride-Stewart, Francis Kalemeera, Amos Massele, Iris Hoxha, Vanda Markovic Pekovic, Guenka Petrova, Konstantin Tachkov, Ott Laius, András Harsanyi, András Inotai, Arianit Jakupi, Svens Henkuzens, Kristina Garuoliené, Patricia Vella Bonanno&, Jakub Rutkowski, Ileana Mardare , Jurij Fürst, Caridad Pontes&, Corinne Zara, Marta Turu Pedrola, Farhana Akter, Hye-Young Kwon, Antony P. Martin&, Rita Banzi, Janney Wale, Jolanta Gulbinovic (Journal of Applied Pharmaceutical Science, 2022)
Sales of medicines continue to grow world-wide driven in part by increasing expenditures on biological medicines leading to concerns with the long-term sustainability of European healthcare systems. The increasing use of biosimilars at lower costs can potentially address this. However, there can be concerns with their prescribing. There are also concerns with biosimilar insulin glargine including concerns with different devices despite increasing sales of long-acting insulin analogues worldwide. Consequently, a need to appraise the European biosimilar market incorporating measures to enhance their use including potential ways to increase the prescribing of biosimilars of insulin glargine at lower costs. Multiple approaches were used to undertake the study including researching measures to enhance biosimilar use and their impact across Europe. In addition, undertake cross national research on the utilization and expenditure of long-acting insulin analogues, which includes biosimilars, principally among Central and Eastern European countries. Multiple demand-side measures across the countries have enhanced the use of biosimilars. There was variable use of biosimilar insulin glargine 100 IU/ml driven by increasing use of patented 300 IU/ml formulations and small price differences between the originator and biosimilars in practice. Overall, multiple demand-side initiatives can appreciably increase biosimilar use benefiting all groups. Additional measures are needed to enhance future prescribing of long-acting biosimilar insulin analogues.
Keywords: Biosimilars, insulin glargine, prices, health policies, demand-side measures, Europe